PENGARUH KOMPRES SEKA TERHADAP PENURUNAN SUHU TUBUH PADA ANAK BALITA YANG MENGALAMI DEMAM DI RSI. SITI RAHMAH PADANG TAHUN 2020 - Miswarti Miswarti (Ensiklopedia of Journal, 2021)
Base on data from the West Sumatera Health Office the incidence of fever in children was 193 cases that occurred in children aged <1 year -14 years, in the Children's Room of RSI. Siti Rahmah Padang found 53 children under five who had fever. When researchers conducted a survey of parents of children, they said that if the body temperature of children under five increased they simply applied cold water and compresses. The purpose of this study was the effect of wiping compresses on decreasing body temperature in children under five with fever at Siti Rahmah Hospital, Padang in 2020. The design of this study was a quasi-experimental with one group pretest-posttest. The sampling technique in this study used purposive sampling with 10 respondents. The research was conducted in November 2019 – May 2020 at Siti Rahmah Hospital, Padang. The results showed that 100% (10 people) had an increase in body temperature before being given a swab and 100% (10 people) had a decrease in body temperature after being given a swab with an average decrease in body temperature of 36.97C. Statistical test results obtained p value = 0.000, where there is an effect of giving a swab compress on the decrease in body temperature of toddlers. Through the Head of RSI Siti Rahmah Padang, she can use the wiping compress as a reference and consideration in making standard operating procedures regarding wiping compresses to reduce body temperature in hospitals